Hubungan penerapan perilaku hidup bersih dan sehat pada tatanan rumah tangga dengan stunting pada balita - Sri Rahmawaty Yasin; Sunarto Kadir; Vidya Avianti Hadju (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is a chronic nutritional problem in children under five years of age due to long-term inadequate nutrient intake characterized by shorter height than other children of the same age. Purpose: To analyze the relationship between the application of clean and healthy living behavior indicators in household settings with stunting in toddlers. Method: Analytic observational research with a cross sectional approach. The population was 124 mothers of toddlers and the sample obtained as many as 95 samples selected by simple random sampling technique through proportional allocation. Independent variables consist of childbirth assisted by health workers, exclusive breastfeeding, use of clean water, use of healthy latrines and not smoking in the house. The dependent variable was stunting in toddlers. The research instrument was a questionnaire that was tested for validity and reliability. Data analysis used chi square test. Results: The study showed that childbirth assisted by health workers (ρ = 0.000), exclusive breastfeeding (ρ = 0.000), use of clean water (ρ = 0.000), use of healthy latrines (ρ = 0.008) and not smoking in the house (ρ = 0001) there is a significant relationship with stunting in toddlers. Conclusion: There is a relationship between the level of implementation of indicators of childbirth assisted by health workers, exclusive breastfeeding, use of clean water, use of healthy latrines and not smoking in the house with stunting in toddlers. Suggestion: For the community to further improve the practice of clean and healthy living behavior in order to improve the degree of public health and support child growth and development.